TINJAUAN HUKUM ISLAM TERHADAP TRADISI MANDI KEMBANG PASCA PERNIKAHAN: Studi Kasus di Desa Maninili Kecamatan Tinombo Selatan Kabupaten Parigi Moutong - sumarna (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2021)
This research discusses the review of Islamic law on the tradition of mandiu pasili (flower bath) in Maninili Village, South Tinombo District, Parigi Moutong Regency. This research is qualitative with an empirical juridical approach, resting on primary data, and is supported by secondary one. Data is collected through observations, interviews, and documentation. This research shows that the tradition of mandiu pasili (flower bath) practiced by Manilili people is not contrary to Islamic law. It is based on the ratio juris that the tradition instead uses idioms and religious values in its implementation. On the other hand, this tradition contains local wisdom that enriches the cultural treasures of Indonesia, loaded with religious values.